Desarrollo de una alternativa de producto utilizando aceites de cocina usados tratados por la empresa Greenfuel Colombia (2020)
The work of degree that develops next in developing an alternative of product already be wax for floors, industrial soap or epoxidized oil; from the used cooking oil (ACUs) treated by the Greenfuel Colombia company in order to expand the market, obtain environmentally friendly products and be a profitable product. The company Greenfuel Colombia, is responsible for the collection and treatment of used and expired oils and fats in order to remove in greater proportion the impurities that are obtained during the cooking and frying process. Initially a characterization of the used cooking oil treated by the company was carried out to evaluate the conditions and the physical and chemical properties in which the raw material is found, the tests that were performed were density, refractive index, iodine index, index of peroxides, saponification index, acidity index, acidity, moisture content and volatile compounds and finally insoluble impurity content. In accordance with the established trials, an experimental development was carried out since the results obtained met the requirements for the preparation of the three selected products which are waxes for furniture and laminate floors, industrial soaps and epoxidized oil. After the development of each product, quality tests were carried out to identify if the product is within the parameters at the industrial level for commercialization.